PENGENALAN BAHASA TULIS BERBASIS PEMEROLEHAN UNTUK ANAK KB DAN TK - Musfiroh, Tadkiroatun (Diksi, 2015)
There are three main aspects of problems concerning the introduction of the written language (the language used in reading and writing activities) in play groups and kindergartens: the method, the learning approach, and the media and sources used for the activities related to it. Inappropriateness in choosing the three aspects will result in undesired development of the children on the whole, including their interest in reading and writing activities. Therefore, there needs to be developed a model for introducing written language for children which accommodates the three aspects. A research study has been conducted with the objective of developing and finalizing such a model and guidelines for its application by means of (1) validation testing by experts and users, (2) limited field testing, and (3) extended field testing. The research subjects were 107 teachers and 178 chidren in play groups and kindergartens in the Yogyakarta Province. The data were obtained by means of various methods: observation, questionnaire, interview, and documentation. The interview data were orthographically transcribed and then combined with fieldnote data and data of the children’s written expressions were documented by using a scanner. The analysis was both qualitatively and quantitatively descriptive. Validity was confirmed by means of intra-rater and inter-rater techniques. The research results indicate that, after validation testing by experts and users as well as limited and extended field testing, the model has shown an ability to improve learning conditions, increase children’s acquisition of the written language for the related productive and receptive language activities, improve their symbol sensitivity, and strengthen the foundations of their reading and writing activities. The application of the model has also improved the teachers’ competence. Keywords: introducing written language, acquisition-based written language, children in play groups and kindergartens